Protein disulfide isomerase-mediated S-nitrosylation facilitates surface expression of P2X7 receptor following status epilepticus - Duk-Shin Lee (Journal of Neuroinflammation, 2021)
Abstract Background P2X7 receptor (P2X7R) is an ATP-gated nonselective cationic channel playing important roles in a variety of physiological functions, including inflammation, and apoptotic or necrotic cell death. An extracellular domain has ten cysteine residues forming five intrasubunit disulfide bonds, which are needed for the P2X7R trafficking to the cell surface and the recognition of surface epitopes of apoptotic cells and bacteria. However, the underlying mechanisms of redox/S-nitrosylation of cysteine residues on P2X7R and its role in P2X7R-mediated post-status epilepticus (SE, a prolonged seizure activity) events remain to be answered. Methods Rats were given pilocarpine (380 mg/kg i.p.) to induce SE. Animals were intracerebroventricularly infused N ω-nitro-l-arginine methyl ester hydrochloride (L-NAME, a NOS inhibitor) 3 days before SE, or protein disulfide isomerase (PDI) siRNA 1 day after SE using an osmotic pump. Thereafter, we performed Western blot, co-immunoprecipitation, membrane fraction, measurement of S-nitrosylated (SNO)-thiol and total thiol, Fluoro-Jade B staining, immunohistochemistry, and TUNEL staining. Results SE increased S-nitrosylation ratio of P2X7R and the PDI-P2X7R bindings, which were abolished by L-NAME and PDI knockdown. In addition, both L-NAME and PDI siRNA attenuated SE-induced microglial activation and astroglial apoptosis. L-NAME and PDI siRNA also ameliorated the increased P2X7R surface expression induced by SE. Conclusions These findings suggest that PDI-mediated redox/S-nitrosylation may facilitate the trafficking of P2X7R, which promotes microglial activation and astroglial apoptosis following SE. Therefore, our findings suggest that PDI-mediated regulations of dynamic redox status and S-nitrosylation of P2X7R may be a critical mechanism in the neuroinflammation and astroglial death following SE.